EFFECT OF SELF-EFFICIENCY ON DECISION MAKING IN SOLVING PROBLEMSOF MATH - Eltalina Tarigan (JURNAL PIONIR, 2019)
This study aim is to see whether there is influence self-efficacy of decision making in solving math problems of SMA Yogyakarta. This research is a quantitative research in which the data obtained by using self-efficacy questionnaire and questionnaire of decision-making in solving math problems given to high school students of Yogyakarta taken at random according to school level amounted to 390 students. Data collection using questionnaire instrument that has been tested its validity with product moment correlation and reliability test by using alpha-cronbach. The data analysis is done by descriptive and simple regression analysis with significant level 0.05. The results of the analysis stated that there is a significant effect of self-efficacy variables on decision-making variables with a significant level of 0.000 <0.05.Keywords: Self-Efficacy and Decision Making Math